Developing genetically engineered mouse models using engineered nucleases: Current status, challenges, and the way forward. (2016) - Lee, Jaehoon; Rho, Jae-il; Devkota, Sushil; Sung, Young Hoon; Lee, Han-Woong
Abstract : The rapid development of engineered nucleases such as zinc finger nucleases (ZFNs), transcription activator-like effector nucleases (TALENs), and the clustered regulated interspaced short palindromic repeats (CRISPR)/CRISPR-associated endonuclease 9 (Cas9) system has ushered in the era of 'renaissance in precision genome engineering' with profound potential to generate mouse models of human diseases. However, with accumulating experience, some drawbacks that we must seriously consider have appeared along with the recent advances in molecular genetics. Here, we highlight recent technical advances of engineered nucleases, discuss the challenges we have faced while using these 'state of the art' genome-editing technologies to generate genetically engineered mouse models (GEMs) and, and look toward the potential future uses of these technologies.